Impact of Dy on structural, dielectric and magnetic properties of Li-Tb-nanoferrites synthesized by micro-emulsion method. Issue 7 (May 2017) - Abbas, Muhammad Khurram; Khan, Muhammad Azhar; Mushtaq, Faiza; Warsi, Muhammad Farooq; Sher, Muhammad; Shakir, Imran; Aboud, Mohamed F. Aly
Abstract: A series of Dy-doped Li–Ni ferrites of the following composition Li0.5 Ni0.48 Tb0.02 Dyx Fe2−x O4 (0.2≤x≥0) was synthesized by the microemulsion method. The X-ray diffraction (XRD) analysis indicated that Li0.5 Ni0.48 Tb0.02 Dyx Fe2−x O4 nano-crystalline ferrites exhibited the single-phase spinel structure. The lattice parameter was determined by the Nelson-Riley refinement technique and it increased by increasing the Dy contents. The crystallite size was computed from the Debye Scherrer's formula and it was in range from 27 to 40 nm. The thermal decomposition process was studied by the thermogravimetric analysis and the annealing temperature observed was 980 °C. The real and complex parts of dielectric constant decreases very sharply in the lower frequency region, but in the higher frequency region, the real and complex part of dielectric constant show variable values with Dy contents. The dielectric tangent loss (tan δ) decreases exponentially with Dy contents. The magnitude of the ac conductivity decreases in certain frequency region, as the Dy contents are increased. The possible mechanisms contributing to the above behavior are discussed. The results of these nanocrystalline ferrites are very suitable materials for microwave device applications.